Indonesian Students’ Interest on Face to Face and Anonymous-Peer Review in Writing Class (International Journal of Educational Technology Research, 2024)
Peer review as a potential pedagogical practice, has gained popularity in university writing classes for ESL/EFL students. The focus in this study is to find out  what  students  prefer  to use face-to-face peer review or anonymous peer review. This study uses a survey research approach as a methodology, the data is carried out by distributing questionnaires to students. The participants are students of SMAN 3 Banjarmasin IPA grade 11. The results of the survey data analysis of student interest in the use of  face-to- face and anonymous peer techniques 59.4% or 19 students prefer anonymous to face-to-face peer review while 40.6% or 13 students choose face-to- face peer review as the best technique in providing feedback in class writing.
Keywords: Writing; Face to Face and Anonymous-Peer Review